A phase II study of oral etoposide in elderly patients with small cell lung cancer. Issue 8 (August 1989) - Smit, E F; Carney, D N; Harford, P; Sleijfer, D T; Postmus, P E
Abstract : Thirty five previously untreated patients with small cell lung cancer older than 70 years were treated with oral etoposide (800 mg/m2 over five consecutive days) every four weeks. Twenty two patients had extensive disease and 13 limited disease. The overall response rate was 71%. The median survival for patients with limited diseases was 16 (range 6-32) months and for patients with extensive disease nine (range 4-17) months. There was mild haematological toxicity and alopecia but no major toxicity. It is concluded that etoposide in this dose regimen is an effective and well tolerated treatment for elderly patients with small cell lung cancer.